Relationship between the Characteristics of e-Commerce Live Streaming and Purchase Intentions: Moderating Effect of Hedonistic Shopping Value - Ying-Ying Wu; Hira Batool; Yao-Jing Yang (Ital Publication, 2024)
E-commerce live streaming has experienced a significant and rapid increase in recent years, establishing itself as a vital catalyst for the growth of the e-commerce business. This research delves into the influence of e-commerce live streaming attributes, namely, authenticity, interactivity, and entertainment, on consumers' purchase intentions. It is based on the Stimulus‒Organism‒Response (SOR) theory and focuses on customer flow experience and hedonic shopping value. To evaluate the study model, the authors gathered survey data from 360 live streaming e-commerce customers and used structural equation modeling. The results indicate that client purchase intentions in e-commerce live streaming are positively influenced by authenticity, interactivity, and entertainment. Authenticity, entertainment, and interaction all contribute to enhancing consumers' flow experience in e-commerce live streaming, with interactivity being the most influential factor. The phenomenon of flow experience has a beneficial impact on the purchasing intentions of clients engaged in e-commerce live streaming. The flow experience serves as an intermediary between the characteristics of e-commerce live streaming and consumers' intentions to make purchases. Hedonic shopping value affects the relationship between the flow experience and the customer's intention to make a purchase. Put simply, when customers have a strong perception of the pleasure they derive from shopping, their intention to make purchases becomes more profound when they are influenced by the state of flow. This study not only contributes to the body of knowledge regarding the correlation between the attributes of e-commerce live streaming and consumer receptiveness, but it also provides businesses and platforms that utilize e-commerce live streaming with actionable recommendations. By improving the content design of live streaming features in e-commerce, customer engagement and immersion are significantly enhanced, establishing a foundation for increasing consumer purchase intention. Doi: 10.28991/ESJ-2024-08-03-018 Full Text: PDF